Bemerkungen zur Gliederung und Paläoklimatologie des oberitalienischen Pleistozäns, insbesondere des Gardasee-Gebietes - Fränzle, Otto (ERDKUNDE, 1961)
The first part of this paper gives a critical analysis of a recent article on the Garda-Region by K. A. Habbe. Here after some highly important fossil soils in Wiirm and Riss loesses are described and paleoclimatologically interpreted. The examples dealt with indicate that not only the tem perature but also, and in a high degree, the drainage is of importance for the development of frost wedges. A reconstruction of the stadial paleoclimate with the aid of these structures implies, therefore, an adequate consideration of the respective soil properties.